Improving parallel irregular reductions using partial array expansion - Gutiérrez, Eladio; Plata, Oscar; Zapata, Emilio L. (Proceedings of the 2001 ACM/IEEE Conference on Supercomputing, 2001)
Much effort has been devoted recently to efficiently parallelize irregular reductions. In this paper, parallelizing techniques for these computations are analyzed in terms of three performance aspects: parallelism, data locality and memory overhead. These aspects have a strong influence in the overall performance and scalability of the parallel code. We will discuss how the parallelization techniques usually try to optimize some of these aspects, while missing the other(s). We will show that by combining complementary techniques we can improve the overall performance/scalability of the parallel irregular reduction, obtaining an effective solution for large problems on large machines. Specifically, a combination of array expansion and a locality-oriented method (DWA-LIP), named partial array expansion, is introduced. An implementation of the proposed method is discussed, showing that the transformation that the compiler must apply to the irregular reduction code is not excessively complex. Finally, the method is analyzed and experimentally evaluated.